INVESTIGATION OF THE EFFECTS OF RUBBERIZED ASPHALT ON DECREASING THE NOISE - Vasile BACRIA; Nicolae HERIŞANU (Fiabilitate şi Durabilitate)
An important contribution to the noise generated by the road transportation means in the environment has the noise produced by the contact between the wheel and the rolling surface. In this paper we present an investigation of the effects of rubberized asphalt on decreasing the noise produced by the contact between the wheel and the rolling surface in the road traffic. In order to characterize the noise we have accomplished measurements in 62 points located near some of the most important crossings from Timisoara City. The results of the measurements were processed, analyzed, interpreted and compared with the admissible values defined by standards.